Applying GQM Approach towards Evaluation of Defect Management in Free/Open Source Software Projects - Gupta, Anu (International Journal of Computer Sciences and Engineering, 2015)
Free/Open Source Software (F/OSS) has emerged as a novel model of software development and distribution during the last decade. An F/OSS project generally evolves by receiving submissions from its volunteers in form of source code, bug identification, feature request, support request, translation request, documentation etc. The present paper uses F/OSS defect data extracted from a research collaboratory. Then it applies Goal/Question/Metric approach to determine the effectiveness of Defect Reporting and efficiency of Defect Resolution. The research findings of present work provide empirical evidences about Defect Management which F/OSS Projects may use to improve software quality.